Eﬀectiveness of Peer-supervision on Paediatric Fever Treatment among Registered Private Drug Sellers in East-Central Uganda: An Interrupted Time Series Analysis - Bagonza, Arthur; Kitutu, Freddy; Peterson, Stefan; Martensson, Andreas; Mutto, Milton; Awor, Phyllis; Mukanga, David; Wamani, Henry (Authorea Preprints, 2020)
Rationale, aims and objectives: Appropriate treatment of paediatric fever in rural areas remains a challenge and may be partly due to inadequate supervision of licensed drug sellers. This study assessed the eﬀectiveness of peer-supervision among drug sellers on appropriate treatment of pneumonia symptoms, uncomplicated malaria and non-bloody diarrhoea among children less than ﬁve years of age in the intervention (Luuka) and comparison (Buyende) districts, in East-Central Uganda. Methods: Data on pneumonia symptoms, uncomplicated malaria and non-bloody diarrhoea among children less than ﬁve years of age was abstracted from drug shop sick child registers over a 12-month period; six months before and six months after introduction of peer-supervision. Interrupted time series was applied to determine the eﬀectiveness of the peer-supervision intervention on appropriate treatment of pneumonia, uncomplicated malaria and non-bloody diarrhoea among children less than ﬁve years of age attending drug shops in East Central Uganda. Results: The proportion of children treated appropriately for pneumonia symptoms was 10.84% (P<0.05, CI = [1.75, 19.9]) higher, for uncomplicated malaria was 1.46% (P = 0.79, CI = [-10.43, 13.36]) higher, and for non-bloody diarrhoea was 4.00% (p <0.05, CI = [-7.95, -0.13]) lower in the intervention district than the comparison district, respectively. Post-intervention trend results showed an increase of 1.21% (p =0.008, CI = [0.36, 2.05]) in the proportion appropriately treated for pneumonia symptoms, no diﬀerence in appropriate treatment for uncomplicated malaria, and a reduction of 1% (p <0.06, CI = [-1.95, 0.02]) in the proportion of children appropriately treated for nonbloody diarrhoea, respectively. Conclusions: Peer-supervision increased the proportion of children less than ﬁve years of age that received appropriate treatment for pneumonia symptoms but not for uncomplicated malaria and non-bloody diarrhoea. Implementation of community level interventions to improve paediatric fever management should consider including peersupervision among drug sellers.
Keywords: Appropriate treatment; Interrupted time series; Peer-supervision; Childhood illnesses; Uganda